Family and labor market choices: Requirements to guide effective evidence-based policy - Anna Kurowska; Michal Myck; Katharina Wrohlich (Institute for the Study of Labor (IZA), 2012)
Microsimulation methods and models of labor market decisions have attracted a lot of attention as an approach to the assessment of consequences of family related policies in the area of labor market and fertility. We set these models in the context of relevant demographic theories and present them from the point of view of their potential as tool to guide effective policy making with the aim to reconcile the objectives of increasing female participation and fertility and reducing poverty levels among families with children.
Keywords: J22; J13; J18; 330; microsimulation; labor supply; fertility; evidence-based policy; Familienpolitik; Mikrosimulation; Fruchtbarkeit; Weibliche Arbeitskräfte; Arbeitsangebot; Familienökonomik